Clinical and histopathological presentations of sinonasal cancers in Komfo Anokye Teaching Hospital - Opoku-Buabeng, Joseph; Acquah, Seth (ENT Updates, 2016)
Objective: To determine the incidence, clinical and histopathological presentations of the paranasal sinus tumors in Komfo Anokye Teaching Hospital, Kumasi, Ghana. Methods: All cases of sinonasal cancers diagnosed between January 2007 and December 2012 were retrospectively reviewed. Results: Of the 68 patients (38 males, 30 females) whose charts were reviewed, the median age was 49 (range: 14 to 84) years. The common clinical presentations were epistaxis (23%), nasal mass (20%), headache (12%), nasal blockage (12%), nasal discharge (11%), proptosis (9%), cheek swelling (8%), and epiphora (5%). The most common histopathological subtypes were squamous cell carcinoma (39.6%) and adenocarcinoma (25%). Conclusion: Sinonasal tumors are frequent in male adults and present with epistaxis, nasal mass, blocked nose and nasal discharge, while squamous cell carcinoma remains the common histopathological type.